Effects of Maternal Swine Appeasing Substance on Growth Performance of Nursery Pigs - Andrew Boschert; Jamil E. G. Faccin; Jordan T. Gebhardt; Joel M. DeRouchey; Robert D. Goodband; Jason C. Woodworth; Raghavendra G. Amachawadi; Teresa Shippy; Mike D. Tokach (Kansas Agricultural Experiment Station Research Reports, 2024)
Two experiments using a total of 640 weanling pigs were conducted to determine the effects of a maternal swine appeasing substance (FerAppease, FERA Diagnostics and Biologicals, College Station, TX) on growth performance, salivary cortisol concentration, and fecal microbiome of nursery pigs. In exp. 1, a total of 360 weanling pigs (DNA 600 × 241; initially 12.6 lb) were used in a 24-d study with five pigs per pen. Due to the potential contact of pigs in adjacent pens transferring the test product, pens were grouped by treatment within the barn and groups were distributed in the barn to minimize this risk. In exp. 1, there were two blocks of pens for each treatment (four total blocks of pens), with each block having 18 pens. In exp. 2, a total of 280 weanling pigs (DNA 600 × 241; initially 12.1 lb) were used in a 45-d study with five pigs per pen in 56 pens split in two rooms. Treatment groups were located in blocks of seven pens to avoid contact between treatment groups, and each treatment was assigned to four blocks (eight blocks total). Block of like treatments was considered the experimental unit for analysis of growth performance data. In both experiments, pens were assigned either a control (placebo of mineral oil) or the appeasing substance (FerAppease, FERA diagnostics and Biologicals, College Station TX). Applications of 3 mL/pig were done at d 0 (weaning) and d 10 by spraying the substance on the forehead of each individual pig. To limit any cross-contamination, either empty pens or the walkway separated the groups to physically segregate treatments from each other. All pigs were fed the same two-phase diet regimens: from d 0 to 10 and d 11 to 24, with phase 3 added in exp. 2 from d 25 to 45. In phase 1 (d 0 to 10, Table 2), control and FerAppease pigs had similar (P > 0.05) ADG, ADFI, and F/G, as well as BW at d 10. Similar results were observed in phase 2 with no evidence of a difference observed between treatments (P > 0.05). For the overall period, when combining phases 1 and 2 (both experiments) and 1, 2 and 3 (only in exp. 2), no differences (P > 0.05) between the two treatments were found for ADG, ADFI, F/G, and BW at d 24 and d 45. Salivary cortisol was measured on d 1 post-weaning and again on d 11 (both 24 h after product administration). There was no evidence (P > 0.10) of a treatment × day interaction or main effect of treatment. Salivary cortisol was greater (P < 0.0001) on d 1 post-weaning compared to d 11 post-weaning. Numerically, on d 1 post-weaning pigs applied with the FerAppease had reduced salivary cortisol concentrations; however, there were no statistically significant differences observed. Fecal samples were collected from two pigs per pen on d 0 and 10, and fecal microbiome analysis did not result in any differences between treatments for alpha or beta diversity, and no meaningful differences were observed in evaluation of class and genus relative abundance data. In summary, the post-weaning application of maternal pheromone to the forehead of nursery pigs post-weaning did not result in any improvements in feed intake, growth rate, feed efficiency, or fecal microbial composition.
Keywords: swine appeasing substance; nursery pig; weaning stress; cortisol